Qualification and spillover effects for geographical indications: the case of Prosciutto di Parma PDO - Giacomini, C. (2013)
The study analyses the spillover effect from Prosciutto di Parma (Parma Ham) PDO to non-PDO ham in the Prosciutto di Parma district. Two distinct networks are identified: a Parma Ham PDO network and a Parma-type ham network. The Parma-type ham network includes producers and a production process similar to the PDO product network but lacking compliance with the PDO code of practice. The paper shows the relationships between the two networks, identifying the geographical and reputational spillover that benefits the Parma type ham producers, their process and reputation.